The Effect of Hand Reflexology Massage on Pain and Fatigue in Patients after Coronary Angiography: A Randomized Controlled Clinical Trial - Nahid Rejeh; Seyed Davood Tadrisi; Shahrooz Yazdani; Kiarash Saatchi; Mojtaba Vaismoradi (Nursing Research and Practice, 2020)
Introduction. Coronary angiography can cause pain and fatigue in patients. Hand reflexology as complementary and integrative care approach has been suggested to help with the reduction of patient’s pain and fatigue. Aim. This study aimed to investigate the effect of hand reflexology on pain and fatigue in patients after coronary angiography. Design. A randomized controlled clinical trial. Methods. This study was conducted on 90 patients in an angiography department of a referral hospital in an urban area of Iran. The patients were randomly divided into two interventions (n = 45) and control (n = 45) groups. Hand reflexology was performed for 20 minutes in the intervention group. Pain and fatigue in the groups were measured immediately, 4 and 6 hours after the intervention. Results. Statistically significant differences were observed in pain and fatigue scores between the groups after the intervention (P=0.001). The intervention had medium to large effects on the patients’ pain and fatigue. Hand reflexology as a nonpharmacological and safe technique can be used by nurses along with other pharmacologic interventions in order to reduce patients’ suffering related to invasive procedures. The trial is registered with IRCT20110912007529N17.